Analisis Bibliometrik Publikasi Penelitian Kearsipan di Indonesia Berbasis Data Scopus - Tupan Tupan (Perpustakaan Nasional, 2023)
The development of archival research in Indonesia can be determined by carrying out bibliometric analysis. The analysis aims to determine the distribution of main information on archival research in Indonesia, journals relevant to archival publications, most cited sources, topic trends based on keywords and treemaps, keyword network maps, and network maps by country. Bibliometric analysis was carried out by using data from Scopus and the keywords (TITLE-ABS-KEY ( archival ) OR TITLE-ABS-KEY ( archives ) OR TITLE-ABS-KEY (archive) AND TITLE-ABS-KEY (Indonesia). Documents obtained were analyzed using R-biblioshiny and VosViewer software. The results of the analysis show that during the years of 1986 to 2023, 462 documents resulting from research on archives in Indonesia were found and published in 351 different sources with an average of 12.31 citations per document. The journal that publishes the most research on archives in Indonesia is the IOP Conference Series: Earth and Environmental Science. Keywords in the field of archives most often used are archives, cultural heritage, Jakarta, conservation, archive, Asia, Bali, breast cancer, colonialism, and decolonization. Trends in topics that are often studied are decolonization, infrastructure, landsat, South Asia, reconstruction, Aceh, colonial, community participation, curriculum, decolonization, fisheries, heritage, deep learning, materiality, tsunami, digital archives, digitalization, and Dutch colonial. Co-occurrence network analysis using VOSviewer produced 4 clusters with 100 keywords with the most archival themes, namely Aceh, anti colonialism, commercialization, decolonization, East Java, fisheries, imperialism, Indian Ocean, and national archives.